IBM DB2 Mirror for i : getting started - Bonhommet, Jean-Luc; Dimmer, Ingo; International Business Machines Corporation. International Technical Support Organization ([Austin, Texas] : IBM Corporation, IBM Redbooks, 2019)
IBM® Db2® Mirror for i provides a new solution for continuous availability for an IBM i environment based on an active-active clustering design that uses a low-latency communication protocol for synchronous database replication. With Db2 Mirror, IBM i customers can benefit from continuous application availability for both planned and unplanned outages. Db2 Mirror can help reduce or eliminate application downtime for regular maintenance operations such as program temporary fix (PTF) installations, operating system (OS) upgrades, or for planned server outages. This IBM Redpaper publication provides a broad overview and understanding of this new solution by covering its architecture, positioning, planning, and implementation aspects. It provides an introduction reference for a seller or technical specialist audience to become familiar with the new Db2 Mirror solution.
Online resource; title from cover (Safari, viewed March 9, 2020).
"This edition applies to IBM i 7.4 (5770-SS1) and IBM Power Systems servers featuring IBM Power8 and IBM Power9 technology"--Page 2 of cover
"REDP-5575-00"--Back cover
Includes bibliographical references.
Keywords: IBM Database 2.; IBM i; IBM Power systems; IBM Database 2; IBM i; IBM Power systems; Database management; Bases de données -- Gestion; Database management